Ліквідність як характеристика фінансового стану сільськогосподарського підприємства - Качула, Світлана Валентинівна; Kachula, Svitlana; Погорелов, Богдан Васильович; Pohorelov, Bohdan (Дніпровський державний аграрно-економічний університет, 2022)
У статті окреслено пошук шляхів удосконалення управління ліквідністю підприємств, та сільськогосподарських в тому числі, з метою підвищення ефективності їх діяльності. У системі фінансового управління сільськогосподарським підприємством в останні роки все більша увага приділяється питанням раціональної організації фінансових потоків, які істотно впливають на кінцеві результати фінансово-господарської діяльності. Така система створюється з метою ефективного використання активів підприємства та джерел їх формування, забезпечення ліквідності та платоспроможності, мінімізації ризиків діяльності та оптимізації витрат на фінансування господарської діяльності. Недостатня ліквідність активів може призвести до неплатоспроможності та банкрутства, а з іншого боку, надлишок ліквідності може викликати зниження рентабельності. Через це сучасна практика вимагає появи дедалі досконаліших процедур проведення аналізу та діагностики ліквідності організації. Аналіз факторів та чинників від яких залежить значення показника ліквідності дозволив зробити висновок, що негативний ефект, який впливає на зниження ліквідності, можна компенсувати за допомогою емісії акцій і додаткового залучення коштів. Покращити перелічені фактори та підвищити ліквідність та платоспроможність підприємства можливо за рахунок злагодженої роботи управлінського персоналу та трудового колективу. The article outlines the search for ways to improve the liquidity management of enterprises, including agricultural enterprises, with the aim of increasing the efficiency of their activities. In the system of financial management of an agricultural enterprise in recent years, more and more attention is paid to the issues of rational organization of financial flows, which significantly affect the final results of financial and economic activity. Such a system is created for the purpose of more rational use of the company's assets and the sources of their formation, ensuring liquidity and solvency, minimizing activity risks and optimizing the costs of financing economic activity. The problem of liquidity management occupies a special place in the financial management system of any organization. The liquidity of an agricultural enterprise is one of the important indicators of the financial condition, and competent management of it will allow not to lose solvency and avoid bankruptcy. A distinctive feature of a reliable and stable organization is its ability to meet its obligations on time and in full. At the same time, regardless of the stage of the life cycle in which the organization is located, management is forced to solve the task of determining the optimal level of liquidity, since, on the one hand, insufficient liquidity of assets can lead to insolvency and bankruptcy, and on the other hand, excess liquidity can cause a decrease in profitability. Because of this, modern practice requires the emergence of increasingly sophisticated procedures for analyzing and diagnosing the organization's liquidity. The analysis of factors on which the value of the liquidity indicator depends has allowed to conclude that the negative effect, which affects the decrease in liquidity, can be compensated with the help of the issue of shares and additional raising of funds. It is possible to improve the listed factors and increase the liquidity and solvency of the enterprise due to the coordinated work of the management staff and the labor team. In the conditions of the modern financial crisis and the ever-increasing level of inflation, a financial-debt type of entrepreneurship has developed, which is manifested primarily in the absence of own capital of enterprises and the presence of sources for their formation. The most urgent are the problems of strengthening payment discipline, bringing the enterprise out of the non-payment crisis and stabilizing the level of agricultural production.
Liquidity as a characteristic of the financial condition of an agricultural enterprise
Keywords: ліквідність; liquidity; платоспроможність; solvency; фінансова стійкість; financial stability; прибуток; profit; коефіцієнти ліквідності; liquidity ratios; рентабельність; profitability